Didaktisko spēļu izmantošana vārda krājuma paplašināšanai bērniem ar garīgās attīstības traucējumiem - Markševica, Vaira (Latvijas Universitāte, 2020)
Darba nosaukums: Didaktisko spēļu izmantošana vārda krājuma paplašināšanai bērniem ar garīgās attīstības traucējumiem. Darba vispārīgs raksturojums, aktualitāte: Valoda ir unikāla, daudzfunkcionāla, vitāli nepieciešama ikvienam, tomēr cilvēks nepiedzimst ar „gatavu valodu” – tā atbilstoši personas iespējām jāveido pakāpeniski, visa mūža garumā. Lai to darītu maksimāli kvalitatīvi, jāņem vērā virkne dažādu faktoru. Tā kā mūsdienās cilvēkiem arvien biežāk tiek konstatēti dažāda veida, smaguma veselības problēmas, tai skaitā, valodas un runas prasmes lietošanas problēmas, garīgās attīstības traucējumi. Visas šīs problēmas ir risināmas, tomēr, jo ātrāk tās konstatē un ātrāk, efektīvāk mēģina novērst, samazināt to negatīvo iespaidu, jo vieglāk tas ir īstenojams. Darba mērķis: izvērtēt didaktisko spēļu nozīmi sākumskolas vecuma bērniem ar garīgās attīstības traucējumiem to vārdu krājuma paplašināšanā. Pētījuma hipotēze: vārdu krājumu bērniem ar garīgās attīstības traucējumiem iespējas paplašināt, ja mācību procesā ņems vērā bērnu vecuma iezīmes, to speciālās vajadzības un stāvokli (tai skaitā, vārdu krājumam un runas īpatnībām) atbilstošākās, piemērotākās metodes. Pētījuma uzdevumi: •analizēt teorētisko literatūru par pētāmo problēmu, •izprast bērnu ar garīgās attīstības traucējumiem raksturojošās iezīmes, •iegūt informāciju un izvērtēt iespējas kā iespējams paplašināt vārdu krājumu, bērniem ar garīgās attīstības traucējumiem, •veikt praktisku pētījumu par vārdu krājuma paplašināšanas iespējām bērniem ar garīgās attīstības traucējumiem, •veikt koriģējoši attīstošo darbību, •apkopot rezultātus, izdarīt secinājumus. Pētījuma metodes: teorētiskā (nozares informācijas apzināšana, analīze), statistikas datu analīze, empīriskais pētījums (bērnu novērošana, bērnu runas logopēdiskā izpēte, pedagoģiskā darbība (koriģējoši – attīstošā darbība), iegūto datu apkopošana un analīze). Atslēgas vārdi: vārdu krājums, garīgie attīstības traucējumi, didaktikā spēle.

Title: Use of didactic games to expand vocabulary for children with mental disabilities. General description of the work, topicality: The language is unique, multifunctional, vital for everyone, yet a person is not born with a "ready-made language" – it must be created gradually according to the capabilities of the person throughout his life. To do this in the best possible quality, a number of different factors must be taken into account. As people nowadays increasingly experience various types of severity health problems, including language and speech use problems, mental disorders. All these problems can be solved, however, the sooner they are identified and the quicker and more effective they are in trying to prevent, reduce their negative impact, the easier it is to implement. Aim of the study: to evaluate the role of didactic games in the development of vocabulary for primary school children with mental disabilities. The research hypothesis: to expand the possibilities of vocabulary for children with intellectual disabilities, taking into account the age characteristics of children, their special needs and the most suitable methods for their situation (including vocabulary and speech). Tasks of the research: •obtain and evaluate the most relevant information on languages and vocabulary; •understand the characteristics of children with mental disabilities; •to obtain information and to consider ways of expanding vocabulary, including for children with intellectual disabilities; •to conduct a practical study on the potential of vocabulary expansion for children with mental disabilities; •summarize results, draw conclusions. Research methods: theoretical (information gathering, analysis), statistical data analysis, empirical research (observation of children, speech therapy of children speech, pedagogical activity (corrective-developmental activity), data collection and analysis). The main conclusion of the study is that in order to expand the vocabulary of children with GAT, as well as to maximize the productivity of daily games, different, very different factors need to be taken into account: the child's GAT collaboration, communication skills, cognitive thinking, perception, attention, memory, etc.), the general level of development of the learner, his or her abilities and state of health, including the child's interests and character. It was also observed that positive emotions contribute to the child's motivation to “participate” in the lesson and gain real, practical benefit from it, that is, the child does not need to be dragged and forced to “learn” but to enjoy the lesson. Equally important is the use of the most appropriate teaching method for each child (which, in turn, must be selected in the light of all the considerations and considerations mentioned above in this paragraph), for example, one game can produce positive results while another is less effective. Keywords: vocabulary, mental retardation, game play.
Use of didactic games to expand vocabulary for children with mental disabilities
Keywords: Pedagoģija; bērni ar GAT; didaktiskā spēle; vārdu krājums; pētījums